State of Evidence-Based Practice in Physician Assistant Education. Issue 1 (March 2018) - White, Dawn M.; Stephens, Phillip
Abstract : Purpose: Evidence-based practice (EBP) involves using the best evidence available to guide patient care. The use of EBP improves patient outcomes and the quality of care delivered. Studies have investigated how EBP is taught in other health professions but not in physician assistant (PA) programs. The purpose of this study was to explore how PA programs teach this subject matter. Methods: After permission was obtained, a survey was adapted from a similar study completed in medical schools. Requests were emailed to 186 accredited PA programs with available contact information. These data were analyzed using descriptive statistics. The text responses were reviewed and summarized to describe how EBP was taught in the programs surveyed. Results: Eighty-four responses were received from the 186 PA programs contacted with the survey request, giving a 45.2% return. Approximately 95% of respondents reported having formal EBP training in their curriculum. Respondents reported formal EBP training through a variety of educational activities, with time spent on these activities ranging from 4 hours to 550 hours. Barriers to implementation of an EBP curriculum were reported by 27% of respondents, with the most common barrier being lack of time. Conclusions: Most PA programs that responded have formal EBP training in the curriculum. There is little standardization regarding the methods used and time spent in these activities. The Accreditation Review Commission on Education for the Physician Assistant may be able to assist in overcoming the reported barriers and improving standardization by implementing a specific EBP accreditation standard.